Crystal structure of 3-phenylpropyl 2-(6-methoxynaphthalen-2-yl)propanoate, C23H24O3 - Wang Li-li; Xue De-dong (Zeitschrift für Kristallographie - New Crystal Structures)
C23H24O3, orthorhombic, P212121 (no 19), a = 5.7576(2) Å, b = 7.7223(4) Å, c = 41.6710(16) Å, V = 1852.77(14) Å3, Z = 4, Rgt(F) = 0.0442, wRref(F2) = 0.1068, T = 170 K.